Sosialisasi pencegahan pernikahan dini sebagai upaya penguatan pendidikan dan kesadaran hukum siswa SMAN 1 Sajira - Saputra, Desma Yuliadi; Mardhiyah Lestari; Reni Apriani; Dina Puspita Sari; Syifaul Inayah; Lulu Annazmi; Dede Putri (Nur Science Institute, 2025)
Child marriage remains a concerning phenomenon in Indonesia, including in Lebak Regency, with serious implications for adolescents' health, education, and socioeconomic conditions, particularly for girls. Multifaceted causes, including low educational attainment, poor family economic conditions, social and cultural pressures, and limited legal awareness, drive this practice. Similar situations are also found among students, including those at SMAN 1 Sajira. In response, the Student Community Service Program (KKM) Group 63 conducted a community engagement activity in the form of a socialization program on preventing child marriage, under the theme